Badania materii organicznej w wybranych rejonach złoża rud miedzi Kopalni Rudna (KGHM PM S.A.) w aspekcie racjonalnej gospodarki złożem i rozwoju zrównoważonego - Delekta, Szymon (My University, 2014)
In order to identify zones of oxidation according to the criteria developed by the Więcław et al. (2007) in Kupferschiefer in Rudna mining area, sampling of 6 profiles was made (giving 29 samples) which were then analyzed by Rock-Eval pyrolysis. Based on the results, genetic type, degree of transformation and the zone of oxidation of organic matter present in Kupferschiefer was recognized. The results of the lowest samples of Kupferschiefer, including the archival data were used for determination of map of zones of oxidation. The most promising area of the operation is the transition zone, which is located in the northern part of the Rudna mining area

W celu identyfikacji stref utleniania wg kryteriów wypracowanych przez Więcława i in. (2007) w łupku miedzionośnym obszaru kopalni miedzi Rudna opróbowano 6 profili złożowych (29 próbek cząstkowych), które poddano analizie pirolitycznej Rock-Eval. Na podstawie wyników badań rozpoznano zawartość, genetyczny typ, stopień przeobrażenia oraz strefę utleniania materii organicznej obecnej w łupku miedzionośnym. Wyniki badań spągowych próbek łupku z uwzględnieniem archiwalnych danych umożliwiły wytyczenie mapy stref utleniania. Najbardziej perspektywicznym obszarem do eksploatacji jest strefa przejściowa, która jest zlokalizowana w północnej części obszaru górniczego OZG Rudna.
The study of organic matter in selected regions of Rudna copper mine (KGHM PM SA) in terms of rational mineral deposit management and sustainable development
Keywords: materia organiczna; łupek miedzionośny; KGHM PM SA; Rock-Eval; rozwój zrównoważony; organic matter; Kupferschiefer; KGHM PM SA; Rock-Eval; sustainable development